2010
DOI: 10.1016/j.brainres.2010.02.075
|View full text |Cite
|
Sign up to set email alerts
|

A morphologically distinct granule cell type in the dentate gyrus of the red fox correlates with adult hippocampal neurogenesis

Abstract: A morphologically distinct granule cell type in the dentate gyrus of the red fox correlates with adult hippocampal neurogenesis Running titleThe dentate gyrus of the red fox Text pages 37Figures 7 Tables 3 Corresponding authorIrmgard In summary, we report a morphologically distinct granule cell type which correlates with adult 3 hippocampal neurogenesis in the fox. Furthermore, the maturation phase of the young neurons may be prolonged as in other long-living species such as primates. SECTIONNervous System De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 70 publications
2
44
0
Order By: Relevance
“…The red fox has surprisingly large numbers of DCX-expressing cells but shows only very moderate proliferative activity in the dentate gyrus 61 . The authors of this study concluded 61 that in this species, the immature -that is, excitable -phase of adult neurogenesis is particularly long, leading to large numbers of DCX-expressing cells (BOX 3).…”
Section: Box 2 | How To Assess Adult Hippocampal Neurogenesis In Humansmentioning
confidence: 99%
“…The red fox has surprisingly large numbers of DCX-expressing cells but shows only very moderate proliferative activity in the dentate gyrus 61 . The authors of this study concluded 61 that in this species, the immature -that is, excitable -phase of adult neurogenesis is particularly long, leading to large numbers of DCX-expressing cells (BOX 3).…”
Section: Box 2 | How To Assess Adult Hippocampal Neurogenesis In Humansmentioning
confidence: 99%
“…For example, in red foxes Amrein and Slomianka [2010] report a correlation coefficient of r = 0.80 (n = 7), while the correlation coefficient in mice as shown by Ben Abdallah et al [2010] is r = 0.98 (correlated means of 6 age classes).…”
Section: Variable Expression Of Markers For Juvenile Neuronsmentioning
confidence: 99%
“…The optical fractionator is a state-of-the-art stereological method to estimate the total number of neurons and has been widely used in a range of brain areas in a variety of species [Amrein and Slomianka, 2010;Gatome et al, 2010a, b;Bhagwandin et al, 2011;Kern et al, 2011]. However, this method has only recently been used to measure the total number and topographic distribution of neurons in retinal wholemounts of tyrant flycatchers [Coimbra et al, 2009] and hydrophiid sea snakes [Hart et al, 2012].…”
Section: Stereological Assessment Of Total Number and Topographic Dismentioning
confidence: 99%